Prevalence of Myocardial Bridge and Possible Associated_x000D_ Variables with Coexisting Coronary Atherosclerosis and_x000D_ Acute Coronary Syndrome - KEPEZ, ALPER; MUTLU, BÜLENT; YEŞİLDAĞ, OSMAN (My University, 2018)
Introduction: The present study aims to evaluate the prevalence of myocardial bridging (MB) and investigate patient andbridge-related factors that may be associated with an increased tendency for atherosclerosis and acute coronary syndrome.Methods: Consecutive coronary angiography recordings that were recorded between 01/01/2013 and 01/01/2016 wereretrospectively evaluated in this study. Data of consecutive patients with MB were obtained from patient files. Patients withMB were grouped according to the presence of significant atherosclerosis in any coronary artery and the presence of significant atherosclerosis proximal to bridge. Patients with isolated MB were also sub-grouped according to their presentationwith the acute coronary syndrome. Demographic, clinical and angiographic parameters were compared between groups.Results: There were a total of 75 patients with MB, with an overall prevalence rate of 1.07%. MB patients without coexistingsignificant atherosclerotic lesion had longer bridge length and more severe stenosis rate (21.4±9.9 mm vs. 17.2±7.6 mm,p=0.045; 73.0±12.5% vs. 65.6±13.0%, p=0.015, respectively). Diabetes mellitus was the only risk factor that was more prevalent in MB patients with significant coexisting atherosclerotic lesions. MB segment of patients with proximal significantatherosclerosis was significantly shorter compared with the length of patients without significant proximal atherosclerosis(16.0±7.4 mm vs 20.7±9.5 mm, p=0.05). The presentation as an acute coronary syndrome was more prevalent in patientswith significant atherosclerosis compared to patients with isolated MB (68.8% vs. 46.5%, p=0.045). There was no significantdiscriminative variable for presentation as acute coronary syndrome in patients with isolated MB.Discussion and Conclusion: The prevalence rate of MB in our study is in agreement with the previous angiographic studiesreported from Turkey. Coexisting atherosclerotic lesions seem to be primarily involved in the pathogenesis of acute coronarysyndrome and ischemic symptoms that had necessitated coronary angiography